A Clostridium Group IV Species Dominates and Suppresses a Mixed Culture Fermentation by Tolerance to Medium Chain Fatty Acids Products - Andersen, Stephen J.; De Groof, Vicky; Khor, Way Cern; Roume, Hugo; Props, Ruben; Coma, Marta; Rabaey, Korneel (Frontiers in Bioengineering and Biotechnology, 2017)
A microbial community is engaged in a complex economy of co-operation and competition for carbon and energy. In engineered systems such as anaerobic digestion and fermentation, these relationships are exploited for conversion of a broad range of substrates into products, such as biogas, ethanol and carboxylic acids. Medium chain fatty acids (MCFA), for example hexanoic acid, are valuable, energy dense microbial fermentation products, however MCFA exhibit microbial toxicity to a broad range of microorganisms at low concentrations. Here we operated continuous mixed-population MCFA fermentations on biorefinery thin stillage to investigate the community response associated with the production and toxicity of MCFA. Here, an uncultured species from the Clostridium group IV (related to Clostridium sp. BS-1) became enriched in two independent reactors that produced hexanoic acid (up to 8.1 gL-1), octanoic acid (up to 3.2 gL-1), and trace concentrations of decanoic acid. Decanoic acid is reported here for the first time as a possible product of a Clostridium group IV species. Other species in the community, Lactobacillus spp. and Acetobacterium sp., generate intermediates in MCFA production, and their collapse in relative abundance resulted in an overall production decrease. A strong correlation was present between the community composition and both the hexanoic acid concentration (p = 0.026) and total VFA concentration (p = 0.003). MCFA suppressed species related to Clostridium sp. CPB-6 and Lactobacillus spp. to a greater extent than others. The proportion of the species related to Clostridium sp. BS-1 over Clostridium sp. CPB-6 had a strong correlation to the concentration of octanoic acid (p = 0.003). The dominance of this species and the increase in MCFA resulted in an overall toxic effect on the mixed community, most significantly on the Lactobacillus spp., which resulted in a decrease of total hexanoic acid concentration to 32  2 % below the steady state average. As opposed to the current view of MCFA toxicity broadly leading to production collapse, this study demonstrates that varied tolerance to MCFA within the community can lead to the dominance of some species and the suppression of others, which can result in a decreased productivity of the fermentation.